Taxonomic revision of the South American subgenus Canthon (Peltecanthon) Pereira, 1953 (Coleoptera: Scarabaeidae: Scarabaeinae: Deltochilini) - Nunes, Luis Gabriel de O.A.; Nunes, Rafael V.; Vaz-De-Mello, Fernando Z. (European Journal of Taxonomy, 2020)
Canthon (Peltecanthon) is revised in this work. The subgenus now includes four species: C. (P.) staigi (Pereira, 1953), C. (P.) haroldi nom. nov., C. (P.) splendidus Schmidt, 1922 and C. (P.) terciae sp. nov. All species occur in the Atlantic Forest. Maps, natural history information, specimen data and illustrations are provided.